2018
DOI: 10.20546/ijcmas.2018.708.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Row Spacing, Varieties and Sowing Dates on Growth and Yield of Pigeonpea

Abstract: to assess the effect of row spacing, varieties and date of sowing on growth and yield of pigeonpea. Significantly higher growth parameters viz., plant height (165.4 cm), leaf area index (2.10), leaf area duration (60.34 days) and crop growth rate (2.39 g m -2 day -1 ) and yield parameters (grain: 940 kg ha -1 and stalk: 4089 kg ha -1 ) were recorded in narrow row spacing (60 cm) compared to wider row spacing (90 and 120 cm). The TTB-7 recorded significantly higher growth viz., plant height (163.6 cm), no. of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…A study by Kithan et al [7] also reported the different flowering and maturing days, plant height and seed yield due to the effect of varietal characteristics in pigeonpea production, where they noted higher yield of variety UPAS 120 (969 kg/ha), among the three tested varieties. The yield variation in pigeonpea due to varietal difference was also noted by Kuri, Chawhan and Rani et al [5,9,14] in their study. A researcher [15] reported that seed yield of pigeonpea depends on source and sink relation which in turn depends on environmental factors.…”
Section: Effect Of Varietysupporting
confidence: 79%
See 2 more Smart Citations
“…A study by Kithan et al [7] also reported the different flowering and maturing days, plant height and seed yield due to the effect of varietal characteristics in pigeonpea production, where they noted higher yield of variety UPAS 120 (969 kg/ha), among the three tested varieties. The yield variation in pigeonpea due to varietal difference was also noted by Kuri, Chawhan and Rani et al [5,9,14] in their study. A researcher [15] reported that seed yield of pigeonpea depends on source and sink relation which in turn depends on environmental factors.…”
Section: Effect Of Varietysupporting
confidence: 79%
“…The late sowing pigeonpea affects seed germination due to higher soil moisture and affects yield due to lower temperature coupled with low rainfall during reproductive and maturity stages [12,13]. The shorter plant and longer days for flowering and maturity and low yield of pigeonpea in late sown as compared to early sown condition were also observed by different authors [5,6,9], where they reported 37%, 397% and 7% more yield under earlier sown condition than later sown condition, respectively. The results of the study are conformity with the findings of [7,13,14], where they found early sowing of pigeonpea was more productive with regard to growth and yield parameters.…”
Section: Effect Of Sowing Datementioning
confidence: 93%
See 1 more Smart Citation
“…However, further increases in row spacing failed to compensate for the reduction in grain yield due to the lower plant density observed by [23]. [24] also found significantly higher total dry matter production in wider row spacing than in narrow row spacing. However, narrow row spacing recorded substantially higher grain and stalk yield per hectare.…”
Section: Discussionmentioning
confidence: 88%
“…This might be owing to availability of more space per plant which leads to better plant geometry. Kuri et al (2018) reported significantly higher number of branches at wider row spacing. Widest row spacing of 100 cm × 20 cm resulted in significantly higher yield attributes of pigeonpea, viz.…”
Section: Yield Of Intercrops × Price Of Intercrop Pey = Grain Yield O...mentioning
confidence: 89%